Some issues of legal regulation of investment activity in agrarian sector of economy of Ukraine - Panchenko, Viktoriia Valeriivna (Problems of legality, 2016)
A study of the current legislation regarding the legal regulation of investment activity in agrarian sector of economy of Ukraine. Clarified the presence of a branching system of normative-legal acts in this area, so to speak of a complete and a mutually agreed system of law is premature. The legislation requires further improvement. After all, to ensure the competitiveness of the agricultural sector of Ukraine’s economy must have a proper legal regulation of relations in the investment process by addressing deficiencies in the investment law, the consolidation of organizational and legal mechanisms of implementation of investment legislation and a clear interaction between public authorities, increase the level of state support for investment activities in agriculture, implementation of appropriate institutional support for the development of the investment market, which will lead to improve the efficiency of agricultural production and the solution of social problems in the village.